Enumerations: data and literary study - Tăranu, Ana (Metacritic Journal for Comparative Studies and Theory, 2020)
In doing so, it resorts to the application of a variety of increasingly complex computational techniques, from "grep", the extraction of regular expressions, for punctuation in the first chapter, to the employment of vector space models and social networks to approximate plot in the second one, to using machine learning to determine the fictionality of a text in chapter four, among others. Each of them is linked to an essential concept or practice of quantitative analysis (repetitive linguistic structures, computational model building, distributional semantics and visual representation of data through diagrams), as it is reframed under the scope of literary methodology. [...]awareness of the repetitions of language can reveal "the ways i n which quantity impinges upon meaning" (18), shifting the traditional preoccupation of literary criticism with "notions of breaks, ruptures and singularities toward questions of stability and duration, to see the deep grooves or furrows of literature, culture, or writers' lives"(i9). [...]quantity gains its significance by providing us with the ability of rendering visible the semantic configurations of cultural practices that "manifest themselves in repetitive, often predictable, and sometimes excessive ways" (3). By acknowledging "both the subjectivity inherent in modeling and a basic instrumentality to reading that has been operative for centuries", the book argues for modelling as a "process of contingent world-making"(12), the main feature of which should be explicitness: "We bring our subjectivity and creativity to a model just as much as we cede portions of our subjectivity to it.